The Gonococcal Genetic Island and Type IV Secretion in the Pathogenic Neisseria - Ramsey, Meghan E.; Woodhams, Katelynn L.; Dillard, Joseph P. (Frontiers in Microbiology, 2011)
Eighty percent of Neisseria gonorrhoeae strains and some Neisseria meningitidis strains encode a 57 kb gonococcal genetic island (GGI). The GGI was horizontally acquired and is inserted in the chromosome at the replication terminus. The GGI is flanked by direct repeats, and site-specific recombination at these sites results in excision of the GGI and may be responsible for its original acquisition. Although the role of the GGI in N. meningitidis is unclear, the GGI in N. gonorrhoeae encodes a type IV secretion system (T4SS). Type IV secretion systems are versatile multi-protein complexes and include both conjugation systems as well as effector systems that translocate either proteins or DNA-protein complexes. In N. gonorrhoeae, the T4SS secretes single-stranded chromosomal DNA into the extracellular milieu in a contact-independent manner. Importantly, the DNA secreted through the T4SS is effective in natural transformation and therefore contributes to the spread of genetic information through Neisseria populations. Mutagenesis experiments have identified genes for DNA secretion including those encoding putative structural components of the apparatus, peptidoglycanases which may act in assembly, and relaxosome components for processing the DNA and delivering it to the apparatus. The T4SS may also play a role in infection by N. gonorrhoeae. During intracellular infection, N. gonorrhoeae requires the Ton complex for iron acquisition and survival. However, N. gonorrhoeae strains that do not express the Ton complex can survive intracellularly if they express structural components of the T4SS. These data provide evidence that the T4SS is expressed during intracellular infection and suggest that the T4SS may provide an advantage for intracellular survival. Here we review our current understanding of how the GGI and type IV secretion affect natural transformation and pathogenesis in N. gonorrhoeae and N. meningitidis.